2013
DOI: 10.1021/es400113y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deficiency and Excess of Zinc on Morphophysiological Traits and Spatiotemporal Regulation of Zinc-Responsive Genes Reveal Incidence of Cross Talk between Micro- and Macronutrients

Abstract: Zinc (Zn) is an essential micronutrient which affects plant growth and development in deficiency and can be toxic when present in excess. In Arabidopsis thaliana , different families of cation transporters play pivotal roles in Zn homeostasis. In the present study, we evaluated the effects of Zn in its deficiency (0 μM; Zn-) and excess (75 μM; Zn++) on various morphophysiological and molecular traits. Primary root length was reduced in Zn- seedlings, whereas there were significant increases in the number and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 71 publications
3
60
0
1
Order By: Relevance
“…Huang et al, 2000 have provided evidence for the involvement of the high affinity Pi transporter (PHT) in the increase of Pi uptake in barley Pi-deficient plants. These results [11, 12] showed that Zn deficiency could induce the expression of the PHT1;1 in Arabidopsis. Recently, genes that are necessary for the increase in Pi overaccumulation in response to Zn deficiency in Arabidopsis have been identified, namely, the Pi exporter PHO1 and its homologue PHO1;H3 [12].…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al, 2000 have provided evidence for the involvement of the high affinity Pi transporter (PHT) in the increase of Pi uptake in barley Pi-deficient plants. These results [11, 12] showed that Zn deficiency could induce the expression of the PHT1;1 in Arabidopsis. Recently, genes that are necessary for the increase in Pi overaccumulation in response to Zn deficiency in Arabidopsis have been identified, namely, the Pi exporter PHO1 and its homologue PHO1;H3 [12].…”
Section: Resultsmentioning
confidence: 99%
“…These variations may be due to the use of different growth conditions such as light, sucrose, incubation time 51, 52 . Also, the concentration of P i 23, 24 and, the use of the various gelling media possessing varying levels of P i contamination may attribute to these variations 52, 53 . Ethylene is known to reduce primary root length under P i -sufficient condition 54–56 .…”
Section: Discussionmentioning
confidence: 99%
“…The nutrient composition of P, Fe, Zn, Mn and Ca plays a crucial role in determining RSA plasticity 24, 53 . Earlier studies reported that the micronutrients deficiency in plants caused by high P condition 19, 20, 47, 48 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Zn, changes in root traits depended more strongly on the applied Zn dose. Lower concentrations of Zn induced lateral root elongation and caused no further changes in RSA (Jain et al, 2013), while higher concentrations inhibited both primary and lateral root growth (Fukao et al, 2011;Richard et al, 2011). However, so far, root architectural responses have always been analyzed separately under Fe deficiency or metal excess (Lequeux et al, 2010;Giehl et al, 2012;Gruber et al, 2013;Jain et al, 2013;Yuan et al, 2013).…”
mentioning
confidence: 99%